Clinical characteristics of 182 pediatric COVID‐19 patients with different severities and allergic status - Du, Hui; Dong, Xiang; Zhang, Jin‐jin; Cao, Yi‐yuan; Akdis, Mubeccel; Huang, Pei‐qi; Chen, Hong‐wei; Li, Ying; Liu, Guang‐hui; Akdis, Cezmi A.; Lu, Xiao‐xia; Gao, Ya‐dong (Allergy (Copenhagen), 2021)
Background The pandemic of coronavirus disease 2019 (COVID‐19) caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection has made widespread impact recently. We aim to investigate the clinical characteristics of COVID‐19 children with different severities and allergic status. Methods Data extracted from the electronic medical records, including demographics, clinical manifestations, comorbidities, laboratory and immunological results, and radiological images of 182 hospitalized COVID‐19 children, were summarized and analyzed. Results The median age was 6 years, ranging from 3 days to 15 years, and there were more boys (male‐female ratio about 2:1) within the studied 182 patients. Most of the children were infected by family members. Fever (43.4%) and dry cough (44.5%) were common symptoms, and gastrointestinal manifestations accounted for 11.0%, including diarrhea, abdominal discomfort, and vomiting. 71.4% had abnormal chest computed tomography (CT) scan images, and typical signs of pneumonia were ground‐glass opacity and local patchy shadowing on admission. Laboratory results were mostly within normal ranges, and only a small ratio of lymphopenia (3.9%) and eosinopenia (29.5%) were observed. The majority (97.8%) of infected children were not severe, and 24 (13.2%) of them had asymptomatic infections. Compared to children without pneumonia (manifested as asymptomatic and acute upper respiratory infection), children with pneumonia were associated with higher percentages of the comorbidity history, symptoms of fever and cough, and increased levels of serum procalcitonin, alkaline phosphatase, and serum interleukins (IL)‐2, IL‐4, IL‐6, IL‐10, and TNF‐α. There were no differences in treatments, duration of hospitalization, time from first positive to first negative nucleic acid testing, and outcomes between children with mild pneumonia and without pneumonia. All the hospitalized COVID‐19 children had recovered except one death due to intussusception and sepsis. In 43 allergic children with COVID‐19, allergic rhinitis (83.7%) was the major disease, followed by drug allergy, atopic dermatitis, food allergy, and asthma. Demographics and clinical features were not significantly different between allergic and nonallergic groups. Allergic patients showed less increase in acute phase reactants, procalcitonin, D‐dimer, and aspartate aminotransferase levels compared with all patients. Immunological profiles including circulating T, B, and NK lymphocyte subsets, total immunoglobulin and complement levels, and serum cytokines did not show any difference in allergic and pneumonia groups. Neither eosinophil counts nor serum total immunoglobulin E (IgE) levels showed a significant correlation with other immunological measures, such as other immunoglobulins, complements, lymphocyte subset numbers, and serum cytokine levels. Conclusion Pediatric COVID‐19 patients tended to have a mild clinical course. Patients with pneumonia had higher proportion of fever and cough and increased inflammatory biomarkers than those without pneumonia. There was no difference between allergic and nonallergic COVID‐19 children in disease incidence, clinical features, and laboratory and immunological findings. Allergy was not a risk factor for developing and severity of SARS‐CoV‐2 infection and hardly influenced the disease course of COVID‐19 in children. There is no difference between allergic and nonallergic children in clinical features and laboratory/immunological findings, and allergy is not a risk factor for COVID‐19. The majority (97.8%) of infected children were not severe, and 24 (13.2%) of them had asymptomatic infections. Laboratory results were mostly within normal ranges, and only a small ratio of lymphopenia (3.9%) and eosinopenia (29.5%) was observed. Higher proportion of patients with pneumonia have fever, cough, comorbidities, and increased inflammatory biomarkers (procalcitonin, alkaline phosphatase and serum interleukins (IL)‐2, IL‐4, IL‐6, IL‐10, and TNF‐α) than those without pneumonia. Abbreviations: AD, atopic dermatitis; AR, allergic rhinitis; AST, aspartate aminotransferase, AURI, acute upper respiratory infection; COVID‐19, coronavirus disease 2019; DA, drug allergy; FA, food allergy; PCT, procalcitonin; SARS‐CoV‐2, severe acute respiratory syndrome coronavirus 2; TNF, tumor necrosis factor.